The Role of Social Media Marketing to Improve the Brand Image of Cakealamanja and Rujak Jambu Cristal Msmes (Case Study at Polbeng Business Expo Chapter II) - Femylda Hidayah; Muhammad Fuad Asrofillah (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This project aims to provide comprehensive support to Micro, Small, and Medium Enterprises (MSMEs), specifically focusing on the business partners Cakealamanja and Rujak Jambu Cristal. This initiative is realized through active participation in the Polbeng Business Expo Chapter II, with the primary objective of optimizing social media marketing strategies to enhance both brand image and digital competitiveness. The project encompasses a series of practical programs, including the creation of professional business profile videos, engaging promotional content, and informative digital product catalogs. Additionally, it involves structured promotional management across social media, the integration of the Quick Response Code Indonesian Standard (QRIS) digital payment system, and intensive mentoring for business owners in preparing standardized financial reports.Methodologically, this project was systematically executed through three primary stages: project preparation (encompassing observation, needs analysis, and planning), project implementation (focusing on marketing execution and the exhibition), and project completion (evaluation and comprehensive reporting). The findings reveal that social media marketing significantly elevates brand visibility, audience engagement, and consumer awareness for both MSMEs. The strategic distribution of creative promotional content across platforms like Instagram, TikTok, and Facebook successfully captured public attention and increased direct consumer traffic.Furthermore, the adoption of the QRIS payment system substantially improved transaction efficiency, speed, and security during the exhibition, effectively meeting the demands of modern consumers. Managerially, the assistance provided in structured financial reporting empowered the MSME owners to transparently understand their business performance, thereby aiding in future financial decision-making. In conclusion, the Polbeng Business Expo Chapter II served as a highly effective platform for advancing MSMEs through a combination of digital marketing and direct business assistance. Ultimately, this project not only delivered a measurable positive impact on MSME sustainability and economic growth but also significantly strengthened the collaborative synergy among students, business owners, and the broader community.